2020
DOI: 10.1007/s10853-019-04190-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-cell energy-absorbing structures with hollow columns inspired by the beetle elytra

Abstract: In this work we propose a new type of thin-walled energy absorbed structure with hollow columns that possesses a design inspired by the beetle elytra. The failure mode of the bionic thin-walled structures is firstly discussed by developing a theoretical model. The energy absorption properties of these bio-inspired multi-call thin-walled structures have been then investigated using nonlinear finite element simulations. The values of the specific energy absorption and the crushing force effectiveness have been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Energy absorption capabilities of the trabecula have also been explored using trabecular‐honeycomb structures and hollow columns. [ 66,67 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy absorption capabilities of the trabecula have also been explored using trabecular‐honeycomb structures and hollow columns. [ 66,67 ]…”
Section: Resultsmentioning
confidence: 99%
“…Energy absorption capabilities of the trabecula have also been explored using trabecular-honeycomb structures and hollow columns. [66,67] Tensile tests were used to evaluate the maximum stress and stiffness of fresh elytra samples. Figure 4C highlights a nonlinear behavior and damage to the elytra of P. diabolicus compared with failure observed in T. dichotomus.…”
Section: Bulk Mechanical Behaviormentioning
confidence: 99%
“…Bionic thin-walled structures [ 8 , 9 ], which are inspired by the design principles of natural structures, have recently attracted wide attention to achieve better crashworthiness and lightweight level, e.g., beetle-inspired structures [ 10 , 11 ], woodpecker-inspired structures [ 12 , 13 ], mantis shrimp-inspired structures [ 14 , 15 ], and shrimp chela structures [ 16 ]. For example, Du et al proposed a novel thin-walled energy absorption structure with hollow columns by studying the beetle elytra [ 17 ]. Zhang et al conducted a systematic review on various biological systems with sophisticated architectures perfectly for impact resistance and energy absorption and conduct dynamic behaviors analysis of each structure from the perspective of design, mechanisms, and models [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Du’s work also provided an important inspiration for the design of the protective structure of the microaerial vehicle. 35 Jeong and Kang presented a novel way to fabricate a metallic foil panel with thickness of 1 mm and evaluated the bending properties of bionic sandwich plate by using the finite element method. They found that the flexural rigidity of metal panel was thousands of times higher than that of the real beetle elytron under different preparation materials and sizes.…”
Section: Introductionmentioning
confidence: 99%